2019
DOI: 10.7554/elife.45160
|View full text |Cite
|
Sign up to set email alerts
|

Attentional amplification of neural codes for number independent of other quantities along the dorsal visual stream

Abstract: Humans and other animals base important decisions on estimates of number, and intraparietal cortex is thought to provide a crucial substrate of this ability. However, it remains debated whether an independent neuronal processing mechanism underlies this ‘number sense’, or whether number is instead judged indirectly on the basis of other quantitative features. We performed high-resolution 7 Tesla fMRI while adult human volunteers attended either to the numerosity or an orthogonal dimension (average item size) o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 112 publications
8
64
0
Order By: Relevance
“…Even if here we have not replicated the direction of the effect originally found by Izard et al (2009) both studies showed a clear asymmetry in looking time as a function of the magnitude's congruency, confirming the ability to generalize quantities across senses. Our results add to this, showing that also preterm newborns, a population at risk of developing deficits in parietal areas known to play a key role in magnitude perception and numerical cognition (Arsalidou and Taylor, 2011;Arsalidou et al, 2018;Bueti and Walsh, 2009;Castaldi et al, 2019;Harvey and Dumoulin, 2017;Harvey et al, 2013Harvey et al, , 2015Piazza and Eger, 2016), are also capable of abstracting quantitative dimensions. Another difficulty for the interpretation of our data arose from the poor spatial and temporal perceptual resolution of the newborns.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Even if here we have not replicated the direction of the effect originally found by Izard et al (2009) both studies showed a clear asymmetry in looking time as a function of the magnitude's congruency, confirming the ability to generalize quantities across senses. Our results add to this, showing that also preterm newborns, a population at risk of developing deficits in parietal areas known to play a key role in magnitude perception and numerical cognition (Arsalidou and Taylor, 2011;Arsalidou et al, 2018;Bueti and Walsh, 2009;Castaldi et al, 2019;Harvey and Dumoulin, 2017;Harvey et al, 2013Harvey et al, , 2015Piazza and Eger, 2016), are also capable of abstracting quantitative dimensions. Another difficulty for the interpretation of our data arose from the poor spatial and temporal perceptual resolution of the newborns.…”
Section: Discussionsupporting
confidence: 73%
“…As with the perception of numerosity, many non-numerical continuous features like quantities and symbolic arithmetical tasks largely involves parietal areas (Bueti and Walsh, 2009;Castaldi et al, 2019;Harvey and Dumoulin, 2017;Harvey et al, 2013Harvey et al, , 2015Piazza and Eger, 2016) that mature slowly with age, making it interesting to measure the functionality of the system underlying magnitude perception in newborns. In this work we compared typical term newborns with preterm newborns, a population at high risk for deficits in the key brain areas subtending this function and characterized by a relatively high rate of arithmetic learning difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Much previous work has assessed interactions between numerical and non-numerical dimensions, with the conclusion that, despite the congruity effects, number is primary (Anobile, Cicchini, & Burr, 2016;Ferrigno et al, 2017;Piazza, De Feo, Panzeri, & Dehaene, 2018). However, it remains unclear whether the relative primacy of numerical, as opposed to non-numerical, information reflects the nature of the number representation, or a difference in perceptual discriminability (Castaldi, Piazza, Dehaene, Vignaud, & Eger, 2019;Melara & Mounts, 1993, 1994. Here, numerosity and cumulative area were matched for discriminability and neither number nor cumulative area was represented at the exclusion of the other.…”
Section: Discussionmentioning
confidence: 99%
“…Eventrelated potential studies also point to the possibility of early and direct encoding of numerical quantities [57,58], with the effect of segregating stimuli into (a number of ) perceptual units arising around 150 ms after stimulus onset [59]. This early numerosity signal may originate in V3/V3A-the first of many areas modulated by attention to number [14].…”
Section: Discussionmentioning
confidence: 99%